Estudo das propriedades estruturais através de espectroscopia Raman de amostras de grafite de poucas camadas (GPC) obtidas por clivagem mecânica - Burgos Gavelán, Ricky Nelson (2011)
In this work, We report studies on samples of graphite few layers obtained from micromechanical techniques of cleaving Manual of highly oriented pyrolytic graphite (HOPG). In order to checking the number of layers in each sample, each was physically characterized by spectroscopic measurements using the Raman technique. We studied the ratio of the intensities of the first-order band permitted G, and the second-order band resonance G′(2D) (IG=I2D), from Raman spectroscopy, provides useful information about stacking of graphite layers to verify the presence of few layers in the samples. The results of this study show that by Raman spectroscopy is possible to obtain information from the structural composition of the material and allows knowing the stacking of graphite layers in the samples. Since was used HOPG, there is no information of the size of crystallite represented by disorder induced D band , since this material has long range crystalline symmetry where the crystal size is much larger than the spot of laser used for the measurements.